Determining The Need for Fire Stations by Backup Double Covering Approach and Location Selection: The Case of Trabzon City - Şeyda Kuku; Ersin Türk (Doğal Afetler ve Çevre Dergisi)
Fire stations are emergency service units that serve for the security of lives and property in urban areas. It is critical for public safety to ensure the highest level of service ensuring a prompt response to the need. However, the land development legislation does not stipulate any provision with regard to the planning of fire stations and the number, size and location of the fire stations will be decided depending on the discretion of respective municipality. But the literature on the planning of fire stations recommends that fire stations must be planned for the entirety of the city based on a set of criteria including response time, coverage area, population density and etc. The objective of this study is to determine the minimum number of fire stations which can serve to the entirety of the planning area within a response time of 5 minutes and that also cover a second fire station as a backup to access within 5, 8, 10 or 15 minutes of response time according the fire risk class of the neighbourhood as indicated in the literature as well as to determine suitable publicly owned plots for such stations based on the master development plan in force. The area selected for this study is that located within the Ortahisar master development plan of the central district of Trabzon. This study will contribute to the determination of the fire station need of the city and site selection process. The findings of this study indicate that the existing fire station must be preserved at its current location, and that two new fire stations are needed which should be situated at eastern and western parts of the city, and also that the Regulation on Production of Spatial Plans must be amended to cover planning of the fire stations.